Infant-level and child-level predictors of mortality in low-resource settings: The WHO Child Mortality Risk Stratification Multi-Country Pooled Cohort - Ahmed, Tahmeed; Ali, Waseem; Argaw, Alemayehu; Bahl, Rajiv; Bailey, Jeanette; Baqui, Abdullah; Becquey, Elodie; Berkley, James A.; Brown, Kenneth; Chisti, Mohammed Jobayer; Chowdhury, Ranadip; Diallo, Hama A.; et al. (Elsevier, 2025)
Background Despite impressive reductions in overall global child mortality, the rate of decline has slowed during the past decade. Current guidelines for the care of paediatric patients in low-resource settings mostly focus on broad clinical syndromes or undernutrition rather than children's individual contextualised risk. We aimed to identify readily assessable child-level characteristics that can predict mortality risk in a range of community and health-care settings in high-burden settings.